A Nonlinear Model to Study Selectively Deformable Wing of an Aircraft - Deiva Ganesh A (Institute of Advanced Engineering and Science, 2015)
Aeroelasticity of an aircraft includes the study of dynamics of prime movers, structural dynamics, and aerodynamics. Research efforts are on in every area to improve the overall performance of an aircraft. In this paper preliminary studies conducted on the dynamics of selectively deformable wing using an under actuated nonlinear model is reported. First, the literature related to the design and analysis of selectively deformable structure (SDS) wing is reviewed. Second, a single degree of freedom (DOF) model to represent a fixed wing and a two DOF under-actuated model to represent SDS are discussed and their mathematical models are derived. Third, the effect of deformable wing portion on the wing dynamics is studied by varying the excitation frequency and stiffness of the model. Fourth, an experimental setup consisting of two rigid links connected by spring and subjected to sinusoidal displacement is investigated. Final section summarizes the research and provides directions for future work.